2007
DOI: 10.1016/j.jvs.2007.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Report on initial experience with transradial access for carotid artery stenting

Abstract: Carotid artery stenting with cerebral protection devices can be safely and effectively performed, with acceptable morbidity and high technical success, by using radial artery access. We recommend obtaining imaging of the aortic arch and supra-aortic trunks with computed tomography, as well as a duplex scan of radial artery, before attempting carotid artery stenting using radial artery access. Further study is needed before recommending that femoral access be replaced by radial access for carotid artery interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 22 publications
0
53
1
4
Order By: Relevance
“…14) A study reported that the intra-arterial administration of 50% isosorbide dinitrate reduced vasospasm or pain, 15) and another report indicated the efficacy of sedation with a venous anesthetic. 13) We performed treatment under general anesthesia to overcome problems regarding pain and to gain better maneuverability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14) A study reported that the intra-arterial administration of 50% isosorbide dinitrate reduced vasospasm or pain, 15) and another report indicated the efficacy of sedation with a venous anesthetic. 13) We performed treatment under general anesthesia to overcome problems regarding pain and to gain better maneuverability.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13] However, according to some studies, when treating left lesions, a guiding system may be drawn into the aortic direction, which depends on the bifurcation angle of the left common carotid artery, making guiding impossible, or it may fall off during the procedure due to its instability. 11,13) In this study, we could navigate a 6 Fr guiding sheath into the common carotid artery using the right radial artery approach in all patients regardless of the left/right side of the targeted blood vessel, and accomplish neuroendovascular treatment postoperative complications. To achieve this, access routes were anatomically evaluated using 3D-CTA, volume rendering MRA, or cerebral angiography before endovascular treatments in all patients.…”
Section: Case Presentationsmentioning
confidence: 99%
“…Several authors have reported CAS without crossing the aorta. 6,7) These techniques require insertion of guide wire into external carotid artery and catheter exchange using long wire. These techniques may be inappropriate for patients with CCA stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…6,7) They have described the use of transbrachial or transradial access, guiding sheath exchange over the long wire using a pigtail or internal mammary artery (IMA) type diagnostic catheter. 6,7) These techniques require insertion of guide wire into external carotid artery 6,7) and may be inappropriate for patients with common carotid artery (CCA) stenosis. To overcome these drawbacks, we developed a novel and simple technique of carotid angioplasty and stenting without crossing the aortic arch, guide wire insertion into external carotid artery, and catheter exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Transradial (TR) approach for coronary and peripheral angiography and angioplasty has become a popular technique [1][2][3][4][5]. The Allen's test (AT), first described in 1929, could be used to determine the presence of collateral flow in the hand [6].…”
Section: Introductionmentioning
confidence: 99%